Contributions from the sociology of social problems around environmental issues. Learning from experiences of extension university and research on risk management - Beltramino, Tamara Lucía (Universidad Nacional del Litoral, 2021)
The article recovers knowledge and operations specific to sociology to contribute to the development of integrated intervention strategies around environmental problems based on research experiences, teaching and outreach on the problem of floods and risk management. To this end, it proposes a denatured view of these phenomena and takes up contributions from social problems theory to address the processes that affect the problematization of the environment in contemporary societies and the role of experts and knowledge scientific in the delimitation and construction of answers for such matters. Finally, it takes up some persistent challenges that are visible in the management strategies of environmental issues in order to enrich the field of debate on these processes and contribute to the deployment of interactoral and transdisciplinary strategies for their management.